The assessment of Food Handlers' Hygiene and Environmental Sanitation in Tofu Home Industry Jombang 2018 - Zamia Floridiana (Universitas Airlangga, 2019)
Food security is an important aspect to produce quality food that is feasible and safe for consumption by general population. Good Manufacturing Product (CPPB) is a guideline in assuring food security adhered in food production process starting from raw materials to storage system. Tofu is highlyIndonesia and it is a product with a short storability or shelf life. Among other protein sources in food, tofu had a greater consumption value of 0.157 kg/ capita/ week in 2017(Badan Pusat Statistik, 2017). The tofu producers include IRT Jombang. The purpose of this study is to analyze the hygiene of food handlers and environmental sanitation based on Peraturan Kepala BPOM RI 2012 about CPPB conducted in IRT Jombang. This research used qualitative research, observational research, and used data collection techniques such as interviews and observations. Interviews were conducted on food handlers and IRT owners while observations were made using an observation sheets. Tofu and clean water were sampled and tested in the laboratory. The results obtained were lack of food handlers hygiene and environmental sanitation. While for laboratory tests on tofu obtained negative results Salmonella sp. and Staphylococcus aureus, and exceeded the maximum limit of Coliform Total and Total Plate Numbers (ALT). Laboratory test results for chemical quality of tofu were negative in formalin and borax. It is recommended to improve monitoring and supervision system of food handlers' hygiene and environmental sanitation in the production environment of tofu home industries